Langmuir Double Probe for Plasma Parameters Measurement - Shrestha, A.K.; Baniya, H.B.; Shrestha, S.; Subedi, D.P. (Kathmandu University Journal of Science Engineering and Technology, 2014)
This paper reports the measurement of electron temperature (Te) and electron density (ne), Debye length (λD), and plasma frequency (fp) in a low-pressure DC glow discharge in air using Langmuir double probe. Three different methods, namely: Double slope, Dote, and Interception, were used to evaluate the electron temperature (Te), and the mean value of Te obtained from the above three methods was used to calculate the electron density, Debye length, and plasma frequency. The main objective of the study is to investigate the effect of discharge voltage and pressure on the plasma parameters at low pressure and low voltage. The experiment showed that (Te), (ne), and (λD) gradually increased, but (fp) decreased on increasing the voltage from 550V to 700V respectively. Similarly, on increasing the pressure from 0.10 to 0.16 mbar, there was a decrease in electron temperature and Debye length, whereas an increase in electron density and plasma frequency.